Correlation of combined B-mode and uterine artery Doppler with the endometrial pathology in perimenopausal women with abnormal uterine bleeding - Kumar, Navjeet; Dhanvij, Minal; Bandyopadhyay, Vedavati; Gupta, Avantika; Sujit Odayath, Nikita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Introduction: Heavy menstrual bleeding in perimenopausal women is defined as excessive blood loss that interferes with the woman's physical, emotional, social, and material quality of life. In India, the reported prevalence of abnormal uterine bleeding is around 17.9%. Background: This study was conducted at AIIMS, Nagpur, where 80 perimenopausal women were recruited with complaints of HMB in our cross-sectional study. We obtained samples of uterine artery PI and RI, endometrial thickness, and performed an endometrial biopsy on the same day. The mean and standard deviation for PBAC, haemoglobin, endometrial thickness, PI, and RI are calculated. Result: The cohort comprised women with a mean age of 46.06 years (±5.8 years). The mean PBAC score was 342 (±117.2), ranging from 145 to 590. Haemoglobin levels were at a mean of 8.8 g/dl (±1.14), with a range from 6.2 gm/dl to 10.3 gm/dl. A mean endometrial thickness of 11.65 mm (±4.05) with mean values for pulsatility index (PI) and resistance index (RI) were 1.72 (±0.065) and 0.75 (±0.035), respectively. Endometrial pathology distribution in biopsy samples included disordered proliferation endometrium in 29 out of 80 cases (36.25%), proliferative endometrium in 21 out of 80 cases (26.3%), secretory endometrium in 14 out of 80 cases (17.5%), and endometrial hyperplasia without atypia in 9 out of 80 cases (11.2%). Additionally, three cases of endometrial malignancy were identified within the cohort. Conclusion: The combination of uterine artery doppler to B-mode ultrasound doesn’t add much information in detecting endometrial pathologies like malignancy and atypia.